(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
A thriving continental economy has kept Botswana stable, but the same cannot be said of collective bargaining. Botswana has limited knowledge and experience with regards to collective bargaining (Mwatcha, 2015). However the country has made efforts to make collective bargaining workable in Botswana. The government of Botswana changed a few labor laws to conform to ILO regulations and international norms. In order to ratify some ILO Conventions, this resulted in the creation of the Public Service Act No. 30 of 2008The PSA merged all employment laws for the public sector, repealing previous acts, namely the “Unified Local Government Service Act, the Teaching Service Act, and Part II A to part II F of the Tribal Land Act” (Government of Botswana, 2008, p. 10). Therefore, the paper seeks to establish the extent to which the legislation supports collective bargaining and the extent to which the legislative framework provides equal power relations between employers and trade unions. Exploring how the legislation support or inhibits collective bargaining could inform collective bargaining legislation reforms at a national level and strategies for effective collective bargaining. The study used a subjective methodology that was known as interpretivism or constructionism, which holds that reality is socially formed and constructed. A sample size of fifteen (15) was purposively selected from trade unions in the public service, the employer (DPSM), the MELSD, industrial court judges, and shop stewards. The study found that the legislation is appropriate and provide equal power relations between bargaining parties albeit few challenge. One of the main challenges is that parties implement what is contrary to provisions of the legislation and another challenge is that the Botswana government monopolizes employment relations. There is a need for capacity building for bargaining parties to implement what is provided in the legislation